CELTIC MYTHOLOGY AS THE FOUNDATION OF THE BRITISH ARTHURIAN EPIC CYCLE (SCIENCE TIME JOURNAL, 2026)
This article explores how Celtic mythology shaped the Arthurian epic cycle and medieval legends of King Arthur and the Knights of the Round Table. It examines themes of heroism, sacred kingship, magic, the Otherworld, and supernatural quests, alongside symbols such as Avalon, Excalibur, and the Holy Grail. The study also analyzes the roles of Arthur and Merlin, the influence of Celtic heroictraditions on knightly ideals, and the Christianization of Celtic myths, highlighting their enduring impact on British culture and modern interpretations of Arthurian legends.